THU0275 Peripheral Neurological Involvement in Primary Systemic Vasculitis. (9th June 2015) - Pena, C.E.; Pera, M.; Marcos, J.; Salas, A.; Testi, A.; Garcia, M.A.
Abstract : Background: Peripheral Neuropathy is reported to be a feature of ANCA- associated vasculitis in up to 58% of patients and is commonly present at the onset of the disease, isolated or associated to other manifestations. Objectives: To evaluate the frequency of the peripheral neuropathy in primary systemic vasculitis and to analyze its clinical and laboratory characteristics as well as the treatments indicated. Methods: This is a descriptive and retrospective study of a cohort of patients with systemic vasculitis, assessed in a rheumatology centre of reference between the years 1999 and 2014. The diagnoses were based on ACR criteria 1990, in accordance with Chapel Hill Conference 2012 nomenclature, or present evidence of small–medium vessels and positive ANCA. We excluded patients with large vessels vasculitis, cryoglobulinemic vasculitis, or secondary forms vasculitis, as well as other neurophatic causes as diabetes, uraemic, alcoholism, vitamin deficiencies or monoclonal gammapathies. Results: 62 patients were registered, 37 were women (59.68%) and 25 men (40.32%). The average age of manifestation was of 49.9±15.9 (18-77).Twenty two patients (37.3%) developed vasculitic peripheral neuropathy.95.5% of them had evidence of other organs compromised and only 4.5% neuropathy alone.8/30 (26.6%) patients with Granulomatosis with Polyangiitis (GPA), 7/11 (63.6%) Eosinophilic Granulomatosis with Polyangiitis (EGPA), 2/11 (18%) microscopic polyangiitis (PAM), 3/3 (100%) of polyarteritis nodosa (PAN) and 4/7 (36.3%) patients who did not meet criteria for classification had peripheral neuropathy. The most frequent manifestation was mononeuritis multiplex (82%). Nerve conduction studies/electromyography was done in 15 cases, showing axonal involvement and predominant axonomielinic compromise. 7/22 patients were biopsied showing inflammatory infiltrations in the vessels walls in six cases, and infiltrations associated with fibrinoid necrosis in one. The laboratory highlighted the presence of increased acute phase reactants: ERS (average 71.38±33.91 mm/h) and CRP (average 63.9±90.5, median 23.5, range 1-364). 41% of the patients were positive for ANCA C, and 22, 7% for ANCA P. The initial BVAS: 18.5±7.74, FFS: 0 (58.8%), 1 (29.4%), 2 (11.7%). There was a statistical association between the peripheral neuropathy compromise and the presence of systemic constitutional symptoms (p 0.01) as well as with mucocutaneous involvement (p 0.04). With regard to the patients' treatment, they all received corticosteroids and 40% received induction therapy with methyl prednisolone pulses. The most used immunosuppressive was cyclophosphamide, followed by azathioprine and methotrexate. Conclusions: The presence of peripheral neurological involvement in primary vasculitis were less common in our cohort than described in literature, being multiplex mononeuritis the most repeated presentation. Vasculitis diagnosis should be ruled out in presence of this manifestation. References: Wolf J. et al. Peripheral Neurophaty as initial manifestation of primary systemic vasculitis. J Neurol (2013) 1061-1070 Haruki K. et al. Clinicopathological features of neurophaty in anti-neutrophil cytoplasmic antibody-associated vasculitis. Cin Exp Nephrol (2013) 17: 683-685 Disclosure of Interest: None declared